Fixed Point Theory and Positive Solutions for a Ratio-Dependent Elliptic System. (1st January 2019) - Liu, Jingmei; Qian, Aixia
Abstract : We consider a ratio-dependent predator-prey model under zero Dirichlet boundary condition. By using topological degree theory and fixed index theory, we study the necessary and sufficient conditions for the existence of positive solutions. Then we present the asymptotic behavior analysis of positive solutions, by bifurcation theory and energy estimates.